'Will anyone who reads this remember that?' E.M. Forster's Encounter with John Addington Symonds' Memoirs as Orientation. - Hueso-Vasallo, Manuel (My University, 2020)
The paper addresses E.M. Forster's encounter with John Addington Symonds' unfinished memoirs. This encounter is regarded through the theoretical concepts of “Orientation” and “Recognition”, analysing how they might contribute to a better understanding of the processes through which queer historiographies are produced. These historiographies, whose genealogies are an important part of my wider PhD thesis, have played a crucial role in the development of both LGBTQ+ identities and of queer criticism at large.
Keywords: Teoría queer; Forster, E.M.- Crítica e interpretación; Sara Ahmed; Rita Felski; Memoirs; John Addington Symonds; E.M. Forster; Queer studies